A non-hygroscopic, highly efficient, dispersed, and highly conductive oil furnace carbon black and its preparation and application
By using inert medium liquid nitrogen in conjunction with indirect cooling water during the preparation of oil furnace carbon black, the reaction is terminated, and the non-hygroscopic high-efficiency dispersed conductive oil furnace carbon black is generated, and the bulk density is increased through paraffin granulation, the problems of strong hygroscopicity and low bulk density of carbon black are solved, and the effect of efficient dispersion and convenient processing is achieved.
Patent Information
- Application Number
- CN202310491617.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-05-04
AI Technical Summary
The existing oil furnace carbon black has strong hygroscopicity during high temperatures, resulting in pores in the plastic extrusion process, affecting the usability of the material. At the same time, the cost of gas-phase carbon black is high, the accumulation density is low, and it is difficult to transport.
The reaction is terminated by inert medium liquid nitrogen and indirect cooling water, and the non-hygroscopic and efficient dispersed conductive oil furnace carbon black is generated, and the bulk density of carbon black is increased by paraffin granulation method.
The problem of pores in carbon black during extrusion is solved, the non-hygroscopicity and dispersion of carbon black are improved, and the bulk density of carbon black is increased through paraffin granulation, which is convenient for transportation and processing.
Smart Images

Figure CN116554714B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive plastics, in particular to a preparation and granulation method of non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black. Background Art
[0002] Carbon black, also known as carbon black, is a kind of amorphous carbon. It is a light, loose and extremely fine black powder with a very large surface area ranging from 10 to 3000m 2 / g, is the product of incomplete combustion or thermal decomposition of carbon-containing substances (coal, natural gas, heavy oil, fuel oil, etc.) under insufficient air conditions. The one made from natural gas is called "gas black", the one made from oil is called "lamp black", the one made from acetylene is called "acetylene black", in addition there are "channel black" and "furnace black". According to the properties of carbon black, there are "reinforcing carbon black", "conductive carbon black" and "wear-resistant carbon black", etc. It can be used as a black dye for the manufacture of Chinese ink, printing ink, paint, etc. It is also used as a rubber reinforcing agent. Most conductive plastics are made by adding high concentrations of filamentous carbon black and completely coked compounds to insulating materials.
[0003] When the oil furnace carbon black on the market is added to plastics during the high temperature process of producing conductive plastics, the carbon black with obvious moisture absorption will produce a large number of pores on the plastic surface during the extrusion process, making the material unusable. The common solution is to use gas phase carbon black to produce conductive plastics, but the cost of gas phase carbon black is high, and the bulk density is small, which is not easy to transport. In order to solve the above problems, a preparation and granulation method of non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a non-hygroscopic, highly dispersed, highly conductive oil furnace carbon black and its preparation and application in order to overcome the defects of the above-mentioned prior art. The produced carbon black has good non-hygroscopicity, which prevents the carbon black from absorbing moisture and solves the problem that a large number of pores will be generated on the plastic surface during the extrusion process of the carbon black, making the material unusable. At the same time, it overcomes the disadvantages of low bulk density of gas phase carbon black and difficulty in transportation and processing.
[0005] The object of the present invention can be achieved by the following technical scheme: A method for preparing non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black, comprising the following steps:
[0006] 1) The air is filtered, pressurized to 50-100kpa, and preheated to 500-900℃, with a flow rate of 8000-15000Nm 3 / h enters the reaction furnace;
[0007] 2) The crude oil is taken out, allowed to settle, filtered to remove impurities in the oil, and transported to a heat exchanger for heating;
[0008] 3) pressurizing the crude oil obtained in step 2) and then spraying it into the reactor in the form of a spray gun along the radial direction of the reactor at the throat section;
[0009] 4) The high-temperature flue gas generated in the combustion section of the reactor reaches a velocity of 50-200 m / s, and the temperature of the combustion section of the reactor reaches 1500-2000° C., which forms a shearing effect on the oil mist generated in step 3), and the high speed and high temperature cause the aromatics in the feed oil to undergo a cracking reaction to form high-temperature carbon black flue gas;
[0010] 5) The material obtained in step 4) is sprayed with inert medium liquid nitrogen in the rapid cooling section of the reaction furnace in coordination with indirect cooling water to terminate the reaction and generate powdered carbon black.
[0011] Furthermore, the fuel used in the reactor in step 1) is natural gas, the pressure of which is 105-110 kpa and the calorific value is 8000-8400 Kcal / m 2 , adjust the ratio of air to natural gas to 16-17:1 according to the volume ratio, that is, the natural gas flow rate is 470-937Nm 3 / h enters the reaction furnace.
[0012] Furthermore, in step 1), the air is pressurized by a multi-stage centrifugal fan and preheated by a high-temperature air preheater before entering the reaction furnace.
[0013] Furthermore, the heat exchanger used in step 2) is a shell and tube heat exchanger, and the heating temperature is 180-200°C.
[0014] Furthermore, in step 3), the pressure of the crude oil pressurized is 3-3.5 MPa, and ten atomizing spray guns are used to allow the crude oil to enter the reaction furnace in a spray state, with a flow rate of 3400-3600 kg / h.
[0015] Furthermore, the reaction time of step 5) is 100ms to 2000ms, and according to the heat exchange method, the flow rate of indirect cooling water is 2000-7000kg / h, and the flow rate of inert medium liquid nitrogen sprayed into the reactor is 5000-12000Nm 3 / h.
[0016] The invention also provides non-hygroscopic high-efficiency dispersed conductive oil furnace carbon black prepared by the method.
[0017] The present invention also provides a granulation method for non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black, which comprises spraying heated paraffin liquid onto powdered carbon black and cooling the powdered carbon black to thereby granulate and produce blocky carbon black.
[0018] Further, the heating temperature of the paraffin wax is 180-220°C;
[0019] The mass fraction of paraffin wax in the powdered carbon black is between 1% and 8%.
[0020] Furthermore, the bulk density of the agglomerated carbon black increases from 0.12 g / mL to 0.2 g / mL compared to the bulk density of the powdered carbon black.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black of the present invention uses inert medium liquid nitrogen in coordination with indirect cooling water to terminate the reaction. This cooling method allows the carbon black to be cooled down in a shorter time, and the inert liquid nitrogen weakens the contact between the carbon black and the air, so that the oxygen-containing functional groups on the surface of the prepared carbon black are sharply reduced. It has good non-hygroscopicity and can prevent the carbon black from absorbing moisture. It solves the problem that a large number of pores are generated on the plastic surface during the extrusion process of carbon black, making the material unusable, and has good practicality.
[0023] 2. The non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black of the present invention has the core feature of using inert medium liquid nitrogen in coordination with indirect cooling water to terminate the reaction, which can reduce the generation of polar oxygen-containing functional groups on the surface of carbon black. The surface of the prepared carbon black exhibits non-polarity, making it easier to disperse and use in plastics such as polyolefins.
[0024] 3. The powdered carbon black of the present invention is granulated to produce block carbon black by spraying and mixing with paraffin at about 200°C, so that the bulk density of the block carbon black granulated with paraffin is significantly improved from 0.12g / mL to 0.2g / mL compared with the bulk density of the powdered carbon black, which is convenient for transportation and processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A solid diagram of powdered carbon black in polypropylene plastic prepared in Example 1 of the present invention;
[0026] Figure 2 It is a solid picture of conventional oil furnace carbon black in polypropylene plastic of Comparative Example 1;
[0027] Figure 3 This is a solid diagram of the powdered carbon black of Example 2 of the present invention and 1% paraffin wax granulated and then added to polypropylene plastic;
[0028] Figure 4 This is a solid diagram of the powdered carbon black of Example 3 of the present invention and 8% paraffin wax granulated and then added to polypropylene plastic;
[0029] Figure 5 A curve diagram showing the resistivity and temperature of the conductive plastic produced by powdered carbon black in Example 1 of the present invention;
[0030] Figure 6The graph is a graph showing the resistivity and temperature of the conductive plastic prepared by granulating powdered carbon black and 1% paraffin wax in Example 2 of the present invention;
[0031] Figure 7 This is a curve diagram between the resistivity and temperature of the conductive plastic prepared by granulating powdered carbon black and 8% paraffin wax in Example 3 of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Unless otherwise specified, the raw materials and equipment used in the present invention are commonly used raw materials and equipment in the art.
[0034] Embodiment 1:
[0035] A method for preparing non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black comprises the following steps:
[0036] 1) After being filtered, the air is pressurized to 80kpa by a multi-stage centrifugal fan and preheated to 800℃ by a high-temperature air preheater with a flow rate of 12000Nm 3 / h enters the reaction furnace;
[0037] 2) The crude oil is taken out, allowed to settle, filtered to remove impurities in the oil, and finally transported to a shell-and-tube heat exchanger for heating;
[0038] 3) pressurizing the crude oil obtained in step 2) and then spraying it into the reactor in the form of a spray in the throat section along the radial direction of the reactor through ten atomizing spray guns;
[0039] 4) The high-temperature flue gas generated in the combustion section of step 3) is flowed at a velocity of 150 m / s, which forms a shearing effect on the oil mist generated in step 3), and the high speed and high temperature cause the aromatic hydrocarbons in the raw oil to undergo a cracking reaction, and the temperature of the combustion section of the reactor reaches 1750° C., forming high-temperature carbon black flue gas;
[0040] 5) The material of step 4) is subjected to the rapid cooling section of the reactor using inert medium liquid nitrogen in combination with indirect cooling water to terminate the reaction and generate powdered carbon black.
[0041] In this embodiment, the fuel used in step 1) is natural gas, the pressure of natural gas is 108kpa, the calorific value is 8200Kcal / m 2 , adjust the ratio of air to natural gas to 16:1 according to the volume ratio, that is, the natural gas flow rate is about 705Nm3 / h enters the reaction furnace, the temperature of heating in the tube heat exchanger in step 2) is 180°C, the pressure of the raw oil pressurized in step 3) is 3.2Mpa, the flow rate of the raw oil entering the reaction furnace in the form of spray is 3500kg / h, the reaction time of step 5) is about 1000ms, and the inert medium liquid nitrogen cooperates with indirect cooling water to terminate the reaction specifically: the indirect cooling water is at a flow rate of 5000kg / h, and the liquid nitrogen is at a flow rate of 8000Nm 3 / h, and sprayed into the reaction furnace at the same time.
[0042] Figure 1 The powdered carbon black produced in Example 1 is directly added to polypropylene plastic, and the amount of powdered carbon black added is 28% of the weight of the polypropylene plastic raw material. According to the conventional preparation method of polypropylene plastic, the raw material is mixed, molded, and finally extruded to obtain a block product. The obtained product is tested for hygroscopicity, and the process is hygroscopic humidity of 80%, hygroscopic time of 24h, and then dried at 200℃ for 5min, and observed and photographed. Figure 1 .from Figure 1 It can be seen that the surface of the polypropylene plastic prepared in this embodiment is smooth and free of bubbles.
[0043] Comparative Example 1:
[0044] The preparation method is the same as that of Example 1, except that the reaction is terminated by direct cooling water, that is, cooling water is sprayed into the reactor at a flow rate of 5000 kg / h, rather than liquid nitrogen in combination with indirect cooling water.
[0045] The oil furnace carbon black produced in Comparative Example 1 was compared with the carbon black produced in Example 1. The oil furnace carbon black of Comparative Example 1 was extruded in polypropylene plastic at 200°C. Figure 2 , it showed very obvious moisture absorption and bubbling characteristics in the hygroscopicity test and could not be used any further.
[0046] Embodiment 2:
[0047] The powdered carbon black produced in Example 1 was regenerated by the following paraffin granulation process:
[0048] The powdered carbon black is brought into the container by gas; and paraffin liquid at a temperature of 200°C is sprayed onto the powdered carbon black, wherein the mass of the paraffin is 1% of the powdered carbon black. The obtained material is cooled and transferred via a conveyor belt, and then granulated to produce blocky carbon black, such as Figure 3As shown, the powdered carbon black produced in this embodiment is granulated with 1% paraffin wax and then added to polypropylene plastic, wherein the amount of 1% paraffin granulated carbon black added is 28% of the weight of the polypropylene plastic raw material. The raw materials are mixed, molded, and finally extruded to obtain a block product. The obtained product is tested for hygroscopicity, and the process is that the hygroscopic humidity is 80%, the hygroscopic time is 24h, and then it is dried at 200℃ for 5min, and observed and photographed as shown in the figure. Figure 3 .from Figure 3 It can be seen that the surface of the polypropylene plastic prepared in this embodiment is smooth and free of bubbles.
[0049] Embodiment 3:
[0050] The powdered carbon black produced in Example 1 was regenerated by the following paraffin granulation process:
[0051] The powdered carbon black is brought into the container by gas; and paraffin liquid at a temperature of 200°C is sprayed onto the powdered carbon black, wherein the mass of the paraffin is 8% of the powdered carbon black. The obtained material is cooled and transferred via a conveyor belt, and then granulated to produce blocky carbon black, such as Figure 4 As shown, the powdered carbon black produced in this embodiment is granulated with 8% paraffin wax and then added to polypropylene plastic. The amount of 8% paraffin granulated carbon black added is 28% of the weight of the polypropylene plastic raw material. The raw materials are mixed, molded, and finally extruded to obtain a block product. The obtained product is tested for hygroscopicity. The process is that the hygroscopic humidity is 80%, the hygroscopic time is 24h, and then it is dried at 200℃ for 5min. Observation and photography are shown in FIG. Figure 4 .from Figure 4 It can be seen that the surface of the polypropylene plastic prepared in this embodiment is smooth and free of bubbles.
[0052] Figure 5 A graph showing the resistivity and temperature of the conductive plastic produced from powdered carbon black in Example 1;
[0053] Figure 6 The graph is a graph of resistivity and temperature of the conductive plastic prepared by granulating powdered carbon black with 1% paraffin wax in Example 2;
[0054] Figure 7 This is a curve diagram between the resistivity and temperature of the conductive plastic prepared by granulating powdered carbon black with 8% paraffin wax in Example 3.
[0055] from Figure 5-7 It can be seen that when the temperature reaches about 120°C, the resistivity of both Example 2 and Example 3 reaches a peak value, the resistivity peak value of Example 3 is about 45Ω / cm, and the resistivity peak value of Example 2 is about 24Ω / cm. The resistance peak value of Example 2 is greater than the resistance peak value of Example 3. Figure 6 and Figure 7As shown; and without adding paraffin (Example 1), the resistivity peak value when the temperature reaches about 120°C is about 80Ω / cm (such as Figure 5 As shown), the conductivity of the conductive plastics is comparable to that of the conductive plastics prepared with gas phase carbon black (commercially available).
[0056] Gas phase carbon black is currently commercially available gas phase carbon black and is commonly used in conductive plastics with the best performance. However, gas phase carbon black has the problems of low bulk density and high price. Oil furnace carbon black can overcome these problems, but the conductivity of conductive plastics prepared by conventional oil furnace carbon black is far inferior to that of gas phase carbon black. The oil furnace carbon black prepared by the method of the present invention can not only overcome the problems of low bulk density and high price of gas phase carbon black, but also can prepare conductive plastics with conductivity comparable to commercial gas phase carbon black, or even better performance. The performance of gas phase carbon black is compared with 8% paraffin granulated carbon black in Example 3, and the results are as follows:
[0057] Table 1 is the performance test table of conductive plastics prepared by gas phase carbon black and paraffin granulated carbon black
[0058] Table 1
[0059]
[0060] It can be seen from Table 1 above that the conductivity of 1% paraffin wax granulated carbon black and 8% paraffin wax granulated carbon black is better than that of gas phase carbon black. At 105°C, the high conductivity advantage of 1% paraffin wax granulated carbon black and 8% paraffin wax granulated carbon black is more obvious.
[0061] Embodiment 4:
[0062] A method for preparing non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black comprises the following steps:
[0063] 1) After being filtered, the air is pressurized to 50kpa by a multi-stage centrifugal fan and preheated to 500℃ by a high-temperature air preheater with a flow rate of 8000Nm 3 / h enters the reaction furnace;
[0064] 2) The crude oil is taken out, allowed to settle, filtered to remove impurities in the oil, and finally transported to a shell-and-tube heat exchanger for heating;
[0065] 3) pressurizing the crude oil obtained in step 2) and then spraying it into the reactor in the form of a spray in the throat section along the radial direction of the reactor through ten atomizing spray guns;
[0066] 4) The high-temperature flue gas generated in the combustion section of step 3) is flowed at a velocity of 50 m / s, which forms a shearing effect on the oil mist generated in step 3), and the high speed and high temperature cause the aromatic hydrocarbons in the feed oil to undergo a cracking reaction, and the temperature of the combustion section of the reactor reaches 1500° C., forming high-temperature carbon black flue gas;
[0067] 5) The material of step 4) is subjected to the rapid cooling section of the reactor using inert medium liquid nitrogen in combination with indirect cooling water to terminate the reaction and generate powdered carbon black.
[0068] 6) The powdered carbon black obtained in step 5) is brought into a container via gas; and paraffin liquid at a temperature of 200° C. is sprayed onto the powdered carbon black, wherein the mass of the paraffin is 3% of the powdered carbon black. The obtained material is cooled and transferred via a conveyor belt to be granulated to produce block carbon black, and the obtained block carbon black is added to polypropylene plastic.
[0069] In this embodiment, the fuel used in step 1) is natural gas, the pressure of which is 105 kPa and the calorific value is 8000 Kcal / m 2 , adjust the ratio of air to natural gas to 16:1 according to the volume ratio, that is, the natural gas flow rate is about 470Nm 3 / h enters the reaction furnace, the heating temperature in the shell and tube heat exchanger in step 2) is 180°C, the pressure of the raw oil pressurized in step 3) is 3Mpa, the flow rate of the raw oil entering the reaction furnace in the form of spray is 3500kg / h, and the reaction time in step 5) is about 100ms.
[0070] The surface of the polypropylene plastic prepared in this embodiment is smooth and free of bubbles.
[0071] Embodiment 5:
[0072] A method for preparing non-hygroscopic and highly efficient dispersed conductive oil furnace carbon black comprises the following steps:
[0073] 1) After being filtered, the air is pressurized to 100kpa by a multi-stage centrifugal fan and preheated to 900℃ by a high-temperature air preheater with a flow rate of 15000Nm 3 / h enters the reaction furnace;
[0074] 2) The crude oil is taken out, allowed to settle, filtered to remove impurities in the oil, and finally transported to a shell-and-tube heat exchanger for heating;
[0075] 3) pressurizing the crude oil obtained in step 2) and then spraying it into the reactor in the form of a spray in the throat section along the radial direction of the reactor through ten atomizing spray guns;
[0076] 4) the high-temperature flue gas generated in step 3) in the combustion section is increased to a flow rate of 200 m / s, which forms a shearing effect on the oil mist generated in step 3), and the high speed and high temperature cause the aromatic hydrocarbons in the raw oil to undergo a cracking reaction, and the temperature of the combustion section of the reactor reaches 2000° C., forming high-temperature carbon black flue gas;
[0077] 5) The material of step 4) is subjected to the rapid cooling section of the reactor using inert medium liquid nitrogen in combination with indirect cooling water to terminate the reaction and generate powdered carbon black.
[0078] 6) The powdered carbon black obtained in step 5) is brought into a container via gas; and paraffin liquid at a temperature of 200° C. is sprayed onto the powdered carbon black, wherein the mass of the paraffin is 6% of the powdered carbon black. The obtained material is cooled and transferred via a conveyor belt, and then granulated to produce block carbon black.
[0079] In this embodiment, the fuel used in step 1) is natural gas, the pressure of natural gas is 110kpa, and the calorific value is 8400Kcal / m 2 , the ratio of air to natural gas is adjusted to 17:1 according to the volume ratio, that is, the natural gas flow rate is about 937Nm 3 / h enters the reaction furnace, the heating temperature in the shell and tube heat exchanger in step 2) is 200°C, the pressure of the raw oil pressurized in step 3) is 3.5Mpa, the flow rate of the raw oil entering the reaction furnace in the form of spray is 3500kg / h, and the reaction time in step 5) is about 2000ms.
[0080] The surface of the polypropylene plastic prepared in this embodiment is smooth and free of bubbles.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing non-hygroscopic and highly efficient dispersed conductive oil furnace black, characterized in that: The following steps are involved: 1) The air is filtered, pressurized to 50-100kpa, and preheated to 500-900℃, with a flow rate of 8000-15000Nm 3 / h enters the reaction furnace; 2) Take out the raw oil, let it settle, then filter it to remove impurities in the oil, and transport it to the heat exchanger for heating; 3) pressurizing the crude oil obtained in step 2) and then spraying it into the reactor in the form of a spray gun along the radial direction of the reactor at the throat section; 4) The high-temperature flue gas generated in the combustion section of the reactor reaches a velocity of 50-200 m / s, and the temperature of the combustion section of the reactor reaches 1500-2000°C, which forms a shearing effect on the oil mist generated in step 3), and the high speed and high temperature cause the aromatics in the raw oil to undergo a cracking reaction to form high-temperature carbon black flue gas; 5) The material obtained in step 4) is sprayed with inert medium liquid nitrogen in the rapid cooling section of the reactor to terminate the reaction and generate powdered carbon black; the reaction time is 100ms to 2000ms, and according to the heat exchange method, the flow rate of indirect cooling water is 2000-7000kg / h, and the flow rate of inert medium liquid nitrogen sprayed into the reactor is 5000-12000Nm 3 / h; 6) Spray the heated paraffin liquid onto the powdered carbon black and cool it to granulate it to produce lump carbon black.
2. The method for preparing a non-hygroscopic, highly efficient, dispersed conductive oil furnace black according to claim 1, characterized in that: The fuel used in the reactor in step 1) is natural gas, with a pressure of 105-110 kpa and a calorific value of 8000-8400 Kcal / m 2 , adjust the ratio of air to natural gas to 16-17:1 according to the volume ratio, that is, the natural gas flow rate is 470-937Nm 3 / h enters the reaction furnace.
3. The method for preparing a non-hygroscopic and highly efficient dispersed conductive oil furnace black according to claim 1, characterized in that: In step 1), the air is pressurized by a multi-stage centrifugal fan before entering the reaction furnace and preheated by a high-temperature air preheater.
4. The method for preparing a non-hygroscopic and highly efficient dispersed conductive oil furnace black according to claim 1, characterized in that: The heat exchanger used in step 2) is a shell and tube heat exchanger, and the heating temperature is 180-200°C.
5. The method for preparing a non-hygroscopic and highly efficient dispersed conductive oil furnace black according to claim 1, characterized in that: Step 3) The crude oil is pressurized to a pressure of 3-3.5 MPa, and ten atomizing spray guns are used to spray the crude oil into the reaction furnace at a flow rate of 3400-3600 kg / h.
6. A non-hygroscopic, highly efficient dispersed conductive oil furnace carbon black prepared by the method of any one of claims 1 to 5.
7. A method for granulating the non-hygroscopic, highly efficient, dispersed conductive oil furnace black according to claim 6, characterized in that: The heated paraffin liquid is sprayed onto the powdered carbon black and cooled to form granules to produce carbon black blocks.
8. The method for granulating non-hygroscopic and highly efficient dispersed conductive oil furnace black according to claim 7, characterized in that: The heating temperature of paraffin wax is 180~220℃; The mass fraction of paraffin wax in powdered carbon black is between 1% and 8%.
9. The method for granulating non-hygroscopic and highly efficient dispersed conductive oil furnace black according to claim 7, characterized in that: The bulk density of carbon black increases from 0.12 g / mL to 0.2 g / mL compared to the bulk density of powdered carbon black.
Citation Information
Patent Citations
Method for producing carbon black for shielding material inside cable
CN109054459A
Method and system for producing acetylene and carbon black, and method and system for producing acetylene and synthesis gas
CN113307716A